2006
DOI: 10.1136/bjo.2005.086595
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age related macular degeneration on quality of life

Abstract: Aims: To describe the impact of age related macular degeneration (AMD) on quality of life and explore the association with vision, health, and demographic variables. Methods: Adult participants diagnosed with AMD and with impaired vision (visual acuity ,6/12) were assessed with the Impact of Vision Impairment (IVI) questionnaire. Participants rated the extent that vision restricted participation in activities affecting quality of life and completed the Short Form General Health Survey (SF-12) and a sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
148
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(165 citation statements)
references
References 15 publications
5
148
2
5
Order By: Relevance
“…8 In a similar study Hassel JB et al it is also stated that on assessing psycho-social impact of ARMD through Impairment of Vision Questionnaire, it was found that patients of ARMD have impairment related to not only reading but also of emotional health, mobility, and participation in relevant activities and their referral to low vision care services is necessary. 9 This all studies showed similar results of impairment as found in our study.…”
Section: Discussionsupporting
confidence: 81%
“…8 In a similar study Hassel JB et al it is also stated that on assessing psycho-social impact of ARMD through Impairment of Vision Questionnaire, it was found that patients of ARMD have impairment related to not only reading but also of emotional health, mobility, and participation in relevant activities and their referral to low vision care services is necessary. 9 This all studies showed similar results of impairment as found in our study.…”
Section: Discussionsupporting
confidence: 81%
“…From age 75, participation decreases strongly [10]. In addition to the effect of aging, vision loss may not only lead to difficulties in performing activities [11][12][13][14][15][16][17] but also to loss of activities [18,19], dependency [20][21][22] and social isolation [23]. Vision loss is related to depression [24][25][26][27] and emotional distress [28] and has a negative impact on health-related quality of life [15,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…3,[6][7][8] The personality traits of a caregiver, as evidenced by this study, include compassion; self-sacrifice; ability to accept additional responsibility; and provide a positive and encouraging environment. This requires a significant degree of commitment by the caregiver and historically, developing a 'compassionate character', for example, in Florence Nightingale's view, specifically underpinned quality of nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant burden of this disease is well established. [6][7][8][9] Caregivers of older persons with AMD have higher than expected distress, particularly if the person has 'wet' AMD. 3,5 The principal cause of vision loss in wet AMD is choroidal neovascularisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation